Cell proliferation in the gastric corpus in Helicobacter pylori associated gastritis and after gastric resection. Issue 3 (March 1995) - Lynch, D A; Mapstone, N P; Clarke, A M; Jackson, P; Dixon, M F; Quirke, P; Axon, A T
Abstract : Patients who have undergone gastric resection are at higher risk of developing gastric carcinoma than normal subjects, and bile reflux is believed to play a role in carcinogenesis. An increase in mucosal cell proliferation increases the likelihood of a neoplastic clone of epithelial cells emerging, particularly where there is chronic epithelial injury associated with bile reflux. Helicobacter pylori is considered a major risk factor for gastric cancer in the intact stomach. It has been shown previously that antral cell proliferation is increased in H pylori gastritis and falls to normal levels after eradication of the organism. Little is known of corpus cell proliferation in H pylori gastritis or after gastric resection. Using in vitro bromodeoxyuridine labelling of endoscopic biopsy specimens we have found that corpus cell proliferation is increased in H pylori gastritis. Cell proliferation was greater in corpus biopsy specimens of resected stomachs than in H pylori gastritis. Subgroup analysis of patients who had undergone gastric resection indicated that those positive for H pylori had higher levels of cell proliferation than those negative for the organism. These findings provide further evidence that H pylori and bile have a role in gastric carcinogenesis and suggest that their presence has a synergistic effect on gastric epithelial cell proliferation.